Haemoglobin glycation index and risk for diabetes-related complications in the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE) trial - van Steen, Sigrid C. (Diabetologia, 2018)
AIMS/HYPOTHESIS: Previous studies have suggested that the haemoglobin glycation index (HGI) can be used as a predictor of diabetes-related complications in individuals with type 1 and type 2 diabetes. We investigated whether HGI was a predictor of adverse outcomes of intensive glucose lowering and of diabetes-related complications in general, using data from the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE) trial. METHODS: We studied participants in the ADVANCE trial with data available for baseline HbA(1c) and fasting plasma glucose (FPG) (n = 11,083). HGI is the difference between observed HbA(1c) and HbA(1c) predicted from a simple linear regression of HbA(1c) on FPG. Using Cox regression, we investigated the association between HGI, both categorised and continuous, and adverse outcomes, considering treatment allocation (intensive or standard glucose control) and compared prediction of HGI and HbA(1c). RESULTS: Intensive glucose control lowered mortality risk in individuals with high HGI only (HR 0.74 [95% CI 0.61, 0.91]; p = 0.003), while there was no difference in the effect of intensive treatment on mortality in those with high HbA(1c). Irrespective of treatment allocation, every SD increase in HGI was associated with a significant risk increase of 14–17% for macrovascular and microvascular disease and mortality. However, when adjusted for identical covariates, HbA(1c) was a stronger predictor of these outcomes than HGI. CONCLUSIONS/INTERPRETATION: HGI predicts risk for complications in ADVANCE participants, irrespective of treatment allocation, but no better than HbA(1c). Individuals with high HGI have a lower risk for mortality when on intensive treatment. Given the discordant results and uncertain relevance beyond HbA(1c), clinical use of HGI in type 2 diabetes cannot currently be recommended. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00125-017-4539-1) contains peer-reviewed but unedited supplementary material, which is available to authorised users.